Language choice considerations of Kadazandusun teenagers in Kota Belud, Sabah - Tham, Fung Ling@Sharen. (Universiti Malaysia Sarawak, UNIMAS, 2008)
This study is undertaken to investigate the language choice considerations among the Kadazandusun teenagers in Kota Belud, Sabah. Specifically, it aims to iden tify the teenagers’ proficiency level in their ethnic language as well as their language choice patterns in daily life communication across the domains of family, education, friendship and religion. In addition , the teenagers’ attitudes toward s their ethni c language are also investigated in shedding light on possible factors that lead to their language choice considerations. To address these objectives, a survey research design utilising questionnaires was employed, covering a total number of 205 Kadazandus un teenagers who were selected from eight secondary schools in Kota Belud. The findings from the study revealed that the Kadazandusun proficiency level among the respondents in four language skills (listening, speaking, reading and writing) is restricted t o performing daily life interactions such as chatting with their siblings and using common expressions in greetings or salutations, in which 40% of the respondents rated their proficiency level as average and another 37% rated themselves at the beginner le vel. In terms of language choice across domains, the findings showed that Kadazandusun is widely used only in the family domain especially when the respondents are communicating with their grandparents (83.4%) and parents (60.5%). In other domains (friends hip, education and religion), the Sabah Malay dialect is the preferred choice as opposed to oth er language or language variety. In the education and religion domain s , the Sabah Malay dialect is chosen mainly due to formality and age difference between resp ondents and their interlocutors . As for language attitudes, the findings from this study showed that the respondents have very positive attitudes toward s Kadazandusun and a majority of the respondents (96.6%) agreed to the importance of preserving the lang uage. This study noted that though the respondents have positive attitudes towards their ethnic language, their use of Kadazandusun in daily life is somewhat limited, which suggest the need for further research to look into this situation.